2022
DOI: 10.3390/ijms232415839
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Phytochemical and Bioactive Compounds and the Antioxidant Properties of Wolfberry during Vinegar Fermentation Processes

Abstract: Wolfberry (Lycium barbarum L.), as a kind of functional fruit, has various nutritional and bioactive components, which exhibit healthy benefits. However, wolfberry is not easy to preserve, and the intensive processing of wolfberry needs to be developed. In the present study, the changes in the phytochemical and bioactive compounds, as well as the antioxidant properties of wolfberry, were evaluated in the brewed processes. We found that the sugar contents were significantly decreased, and the total acids values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Proline and histidine are the main amino acids in Goji fruit wine. During the fermentation of fruit vinegar, histidine increased significantly, while proline and alanine content decreased significantly ( Xia et al, 2022 ). Altogether, fermentation of fruits could produce various active ingredients superior to those of fruit and vegetable raw materials, such as enzymes, organic acids, peptides, oligosaccharides, vitamins, flavonoids, polyphenols, amino acids, natural antibiotics, minerals, polysaccharides, as well as antioxidant components such as γ-aminobutyric acid (GABA), superoxide dismutase (SOD), catalase, etc., to increase its commercial value.…”
Section: The Beneficial Effect Of Fruit Fermentationmentioning
confidence: 99%
“…Proline and histidine are the main amino acids in Goji fruit wine. During the fermentation of fruit vinegar, histidine increased significantly, while proline and alanine content decreased significantly ( Xia et al, 2022 ). Altogether, fermentation of fruits could produce various active ingredients superior to those of fruit and vegetable raw materials, such as enzymes, organic acids, peptides, oligosaccharides, vitamins, flavonoids, polyphenols, amino acids, natural antibiotics, minerals, polysaccharides, as well as antioxidant components such as γ-aminobutyric acid (GABA), superoxide dismutase (SOD), catalase, etc., to increase its commercial value.…”
Section: The Beneficial Effect Of Fruit Fermentationmentioning
confidence: 99%
“…Due to the raw materials and fermentation, the products contain a variety of nutritional and active components, such as organic acids, amino acids, and polyphenols [90,91]. Some studies have reported that fruit vinegar has the effects of antibacterial and antioxidant activities, anti-aging, and anti-fatigue [92][93][94].…”
Section: Wolfberry Fruit Vinegarmentioning
confidence: 99%
“…Therefore, the combination of epiphytic LAB inoculants with S. bovis would improve mulberry silage quality and antioxidant capacity by affecting the bacterial community, hence producing different metabolites such as flavonoids (He et al, 2021 ; Xia et al, 2022b ). The food fermentation system inoculated with LAB could increase bioactive compounds (such as phenolics and flavonoids) and antioxidant capacity (Kim and Jang, 2011 ; Xia et al, 2022a ). However, the mechanism of how epiphytic LAB affected silage quality and antioxidant capacity by altering the microbial community and metabolite composition is still unclear.…”
Section: Introductionmentioning
confidence: 99%